Jayawickrama, N. A., The Chronicle of the Thūpa and the Thūpavamsa. Being a Translation and Edition of Vācissarathera’s Thūpavamsa. Luzac & Company Ltd., Londres, 1971. - G. S., S. (Estudios de Asia y África, 1973)
-